2009
DOI: 10.1097/tp.0b013e318198dbc7
|View full text |Cite
|
Sign up to set email alerts
|

CD3+-Mediated Rejection and C4d Deposition in Two Composite Tissue (Bilateral Hand) Allograft Recipients After Induction With Alemtuzumab

Abstract: These findings suggest that alemtuzumab may not prevent cell-mediated rejection of a hand allograft transplant. Furthermore, C4d deposition warrants attention in clinical composite tissue allotransplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…For instance, although Landin et al (13) reported positive C4d allograft staining during acute rejection of a hand transplant, it was in the absence of DSA and found to also be present in unaffected areas or at times of no clinical rejection. Similarly, in a series of six hand recipients, Kaufman et al (7) reported C4d staining to be ''nonspecific and uninformative'' in five of the recipients; the sixth recipient was thought to have C4d staining specific to the allograft but in the absence of DSA (7).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although Landin et al (13) reported positive C4d allograft staining during acute rejection of a hand transplant, it was in the absence of DSA and found to also be present in unaffected areas or at times of no clinical rejection. Similarly, in a series of six hand recipients, Kaufman et al (7) reported C4d staining to be ''nonspecific and uninformative'' in five of the recipients; the sixth recipient was thought to have C4d staining specific to the allograft but in the absence of DSA (7).…”
Section: Discussionmentioning
confidence: 99%
“…Patients: Detailed descriptions of patients and the clinical courses were published previously (3)(4)(5)11,12). In brief, five patients (four male and one Efomycine M: Efomycine M was purified as described earlier (15,16 Figure 1F) and did not correlate with severity of rejection (cc = −0.071).…”
Section: Investigation Of Human Hand Allograft Skin Biopsiesmentioning
confidence: 99%
“…A similar situation has been observed in a recalcitrant infection due to human papilloma virus (HPV) in the allograft of a recipient of HA, that required aggressive treatment due to viral resistance [40]. A repetitive cutaneous varicella zoster infection was also observed in a HA recipient, requiring long-term prophylaxis with acyclovir [30]. Other recipients of FAs have shown non-systemic worrying infection due to herpes simplex virus (HSV) at the lip [23 • …”
Section: Importance Of Infectionmentioning
confidence: 86%
“…It is also unclear whether antibodies play a significant role in rejection of VCAs. Marker of antibody mediated rejection (AMR) C4d has been found by a few teams in the allografts, but others were not able to determine [30,34]. The team from Louisville was able to determine that DSA raised after HA removal due to CR [31, 32 • ].…”
Section: Importance Of Rejectionmentioning
confidence: 99%